Pulmonary Function Test: A Mainstay for Evaluating Respiratory Health in Patients Recovered from COVID-19 Infection - Sanjay Nehe; Avinash Taksande; Ranjit Ambad; Nandkishor Bankar; Noman Obaid (Journal of Pharmacy and Bioallied Sciences)
Background: Despite of millions of people who suffered from coronavirus disease 2019 (COVID-19) infection, pulmonary functions of these patients are sparsely reflected in the literature. Although few researchers have performed pulmonary function tests to evaluate the respiratory function of COVID-19 patients after recovery from acute illness, the sample size was too limited. The present study was conducted in a tertiary care hospital with an aim to determine pulmonary functions of COVID-19 patients recovered from acute illness. Methods: A total of 250 COVID-19 patients who recovered from acute illness were included in the study. Pulmonary function test of these patients was performed; the indices of PFT studied included, forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), and FEV1/FVC ratio. Results: Even after >3 months of recovery from the COVID-19 acute illness, patients had respiratory complaints like cough and shortness of breath. These convalescent patients also reported to have certain psychological issues like feeling of loneliness, fear, anxiety, and depression. It was noted that all the respiratory parameters of patients even after >3 months of recovery from the COVID-19 acute illness were compromised. Conclusion: The pulmonary functions of the patients recovered from COVID-19 infection should be evaluated before discharge of the patient from hospital followed by periodic evaluation post discharge, so that necessary therapeutic interventions can be initiated. Breathing exercises and pranayama can augment the better outcome of these patients. Pulmonary function tests are not only recommended but also are necessary for monitoring of patients who have recovered from COVID-19 infection.